Penerapan Telenursing pada Pasien dengan Diabetes Melitus Selama Pandemi COVID-19 - Angela Librianty Thome (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze telenursing in diabetes mellitus patients during the COVID-19 period. The method used is a literature review which begins with keywords to facilitate search and the ProQuest, Pubmed, and Google Scholar databases. The results showed that there were 16 articles analyzed from 4 articles on ProQuest, two articles on Pubmed, and 10 on Google Scholar. Telenursing has been implemented in several countries, and some are through telenursing applications. In conclusion, telenursing makes it easier for patients to get information about treatment, prevention, and education about diabetes during the COVID-19 pandemic. Keywords: COVID-19, Diabetes Mellitus, Telenursing